Self-Assessment of Professional Growth Through Reflective Portfolios - Nickel, Jodi (Phronesis, 2013)
This study aims to discern how teacher candidates develop reflective capacity by self-assessing their portfolios. While the goal was to help first-year teacher candidates assess their progress toward achieving provincial teaching competencies, many called attention to the interconnections between their academic artifacts and their personal profiles. This led the researcher to refine the focus of the portfolio to the emergence of professional identity and developing structures to support this type of self-awareness.